The Adaptation of the Normative to Regulate the Fracking Technique: the Spanish Case - Garrido de las Heras, Santiago (2014)
The authors bring us a general approximation of the regulatory model related to hydrocarbon exploration and production activities in Spain. In this sense, the analysis is focused in the increased use of the hydraulic fracturing technique, better known as «fracking». In particular, the authors analyze the case of the refusal of some Spanish Autonomous Communities regarding the implementation of this technique and how the Central Government has faced that opposition.